Kebarangkalian Peristiwa Pelengkap

 
13.3  Kebarangkalian Peristiwa Pelengkap
 

Kebarangkalian bagi peristiwa pelengkap suatu peristiwa, \(P(A')\)

\(\begin{aligned} P(A) + P(A') &= 1 \\\\ P(A') &= 1- P (A) \\\\ \end{aligned}\)

dimana \(0 \le P(A) \le 1\).

 

 

Kebarangkalian Peristiwa Pelengkap

 
13.3  Kebarangkalian Peristiwa Pelengkap
 

Kebarangkalian bagi peristiwa pelengkap suatu peristiwa, \(P(A')\)

\(\begin{aligned} P(A) + P(A') &= 1 \\\\ P(A') &= 1- P (A) \\\\ \end{aligned}\)

dimana \(0 \le P(A) \le 1\).